A systematic review of rescue analgesic strategies in acute exacerbations of primary trigeminal neuralgia. (August 2019) - Moore, D.; Chong, M.S.; Shetty, A.; Zakrzewska, J.M.
Abstract: Background: Trigeminal neuralgia (TN) can have a significant impact on wellbeing and quality of life. Limited data exist for treatments that improve TN pain acutely, within 24 h of administration. This systematic review aims to identify effective treatments that acutely relieve TN exacerbations. Methods: We searched Medline and Cochrane Central Register of Controlled Trials (CENTRAL) for relevant English language publications. The reference list for all articles was searched for other relevant publications. All studies that satisfied the following PICO criteria were included: (i) Population—adults with acute exacerbation of primary TN symptoms; (ii) Intervention—any medication or intervention with the primary goal of pain relief within 24 h; (iii) Comparator—usual medical care, placebo, sham or active treatment; (iv) Outcome—more than 50% reduction in pain intensity within 24 h of administration. Results: Of 431 studies, 17 studies were identified that reported immediate results of acute treatment in TN. The evidence suggests that the following interventions may be beneficial: local anaesthetic, mainly lidocaine (ophthalmic, nasal or oral mucosa, trigger point injection, i.v. infusion, nerve block); anticonvulsant, phenytoin or fosphenytoin (i.v. infusion); serotonin agonist, sumatriptan (s.c. injection, nasal). Other referenced interventions with very limited evidence include N -methyl-d -aspartate receptor antagonist (magnesium sulphate infusion) and botulinum toxin (trigger point injection). Conclusions: Several treatment options exist that may provide fast and safe relief of TN. Future studies should report on outcomes within 24 h to improve knowledge of the acute analgesic TN treatments.